Sosialisasi Pola Asuh Orangtua bagi Perkembangan Sosial Emosional Anak - Annisa Mutiara Vani; Yulianto, Dema; Iswantiningtyas, Veny (Universitas Nusantara PGRI Kediri, 2022)
Social-emotional development has a very important role in a child's life. Emotions are a form of communication for children to convey their feelings and needs to others. In addition, emotions can also influence children to make adjustments to their social environment. To optimize the social emotional development of children, parenting is needed. Socialization activities for parenting parenting for social emotional development is to increase knowledge for parents. Socialization participants are expected to be able to practice the material that has been socialized to parents and their children in their daily lives, so that children are able to control their emotions and are able to socialize in their lives. The socialization was carried out using direct observation, interviews and socialization methods (small seminars and training). As a result of these activities, participants